Preparation, Surface Activities, and Biodegradability of a Bola‐Type Collagen Hydrolysate‐Based Siloxane Surfactant. Issue 3 (15th April 2018) - Wang, Baochuan; Liu, Jun; Han, Xiaona; Li, Fengdi; Li, Zhengjun; Yang, Qinhuan
Abstract: 2 bola‐type collagen hydrolysate‐based siloxane surfactants (CBES) were prepared via grafting of an epoxy‐terminated polydimethylsiloxane oligomer onto 2 collagen hydrolysates with different molecular weights. Their structure was characterized by Fourier transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance ( 1 H NMR) spectroscopy, and the degree of grafting was determined by calculating the free amino content, which confirmed the successful synthesis of CBES. Subsequently, their physicochemical properties, such as particle size and isoelectric point, were evaluated. Besides, surface activities, application functionalities, and biodegradability of CBES were investigated. The results showed that CBES‐1, prepared with the lower‐molecular‐weight collagen hydrolysate, possessed superior surface activity, excellent foaming ability, and good emulsifying capacity comparable to those of a typical emulsifier such as the fatty alcohol polyoxyethylene ether (AEO‐9). In addition, their BOD5 /CODCr value and CO2 evolution demonstrated that the CBES are readily biodegradable. There is, therefore, great potential for the bola‐type CBES to be applied in fields such as leather treatment and textile industries.